2022
DOI: 10.1186/s12873-021-00561-w
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of emergency neurosurgical TBI procedures: a population-based study

Abstract: Background The rates of emergency neurosurgery in traumatic brain injury (TBI) patients vary between populations and trauma centers. In planning acute TBI treatment, knowledge about rates and incidence of emergency neurosurgery at the population level is of importance for organization and planning of specialized health care services. This study aimed to present incidence rates and patient characteristics for the most common TBI-related emergency neurosurgical procedures. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…In the multivariable model, strong positive factors in both groups were younger age, pre-injury ASA-score 1–2, severe TBI, severe disability due to TBI upon discharge, in line with a previous study ( 14 ). We cannot fully explain the variation regarding male sex, but contributing factors may be that in younger TBI patients, males are over-represented and males more often need emergency neurosurgery ( 29 , 30 ). Interestingly, we found a difference in favour of the group who received neurosurgical procedure with ICP-sensor insertion in the pandemic group, although the difference was not statistically significant.…”
Section: Discussionmentioning
confidence: 96%
“…In the multivariable model, strong positive factors in both groups were younger age, pre-injury ASA-score 1–2, severe TBI, severe disability due to TBI upon discharge, in line with a previous study ( 14 ). We cannot fully explain the variation regarding male sex, but contributing factors may be that in younger TBI patients, males are over-represented and males more often need emergency neurosurgery ( 29 , 30 ). Interestingly, we found a difference in favour of the group who received neurosurgical procedure with ICP-sensor insertion in the pandemic group, although the difference was not statistically significant.…”
Section: Discussionmentioning
confidence: 96%
“…The Brain Trauma Foundation guidelines do not state an upper age limit for neurosurgical care [ 4 ]; however, studies have found advanced age to be associated with lower treatment intensity, and the incidence of emergency neurosurgery has been found to peak at age 75 [ 18 , 42 , 43 ]. Our study identified a rapid decrease in transfer probability at the same ages.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, care should be taken to make inferences about atypical patients. Sixth, highly relevant information about neurosurgical interventions among patients who underwent transfer was unfortunately not available from the NTR but has been studied elsewhere [ 43 ]. Neurosurgical procedures are not performed outside NTCs in Norway.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical trial will be carried out at the TBI outpatient clinic at the Department of Physical Medicine and Rehabilitation, Oslo University Hospital (OUH), the trauma referral centre in South-East Norway [ 28 ]. Patients are referred to the TBI outpatient clinic from the Emergency department, Neurosurgical department, and from general practitioners.…”
Section: Methods: Patients Interventions and Outcomesmentioning
confidence: 99%